2019
DOI: 10.3389/fpls.2018.01973
|View full text |Cite
|
Sign up to set email alerts
|

St. John’s Wort (Hypericum perforatum) Products – How Variable Is the Primary Material?

Abstract: Background: Saint John’s wort (Hypericum perforatum L., HP) is commonly registered in Europe under the THR scheme (Traditional Herbal Registration) or licensed as a medicine. Nonetheless unregulated medical products and food supplements are accessible through the internet which are often of poor quality. The species’ natural distribution stretches through large regions of Europe to China and four subspecies have been distinguished. When compared to the European Pharmacopoeia reference, the presence of addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 18 publications
1
19
0
4
Order By: Relevance
“…This is similar to previous findings from our group, e.g. on St. John’s wort and roseroot ( Booker et al, 2016 ; Scotti et al, 2019 ) where in general, the main chemical variability was shown to be due to differences in the value chains of the products. It shows that it is worth investigating the possibility of cultivating herbal materials globally combined with an appropriate and sustainable processing method, instead of cultivating in the “traditionally authenticated” herbal materials region.…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to previous findings from our group, e.g. on St. John’s wort and roseroot ( Booker et al, 2016 ; Scotti et al, 2019 ) where in general, the main chemical variability was shown to be due to differences in the value chains of the products. It shows that it is worth investigating the possibility of cultivating herbal materials globally combined with an appropriate and sustainable processing method, instead of cultivating in the “traditionally authenticated” herbal materials region.…”
Section: Discussionsupporting
confidence: 92%
“…The composition of extracts from H. perforatum has been studied extensively and many secondary metabolites including rutin, hyperforin, hyperoside, quercitrin, isoquercitrin, quercetin, hypericin, and chlorogenic acid, have been identified [ 3 , 15 , 16 , 17 ]. Nevertheless, two compounds have emerged as the most important for the pharmaceutical industry: hyperforin and hypericin.…”
Section: The Relevance Of Hyperforin Hypericin and Other Bioactivmentioning
confidence: 99%
“…Each of these constituents is usually present in low amounts, with occasional exceptions mainly due to the ample variability of the primary material ("materia prima"). For instance, rutin can reach significant concentrations in Hypericum perforatum of Chinese origin, but on the other hand it is absent in other SJW samples [86]. It is also worth noting that the sum of the amounts of the single minor flavonoid components of SJW may often reach levels high enough to provide a biologically significant antioxidant potential [85].…”
Section: Sjw and Its Componentsmentioning
confidence: 99%